2022
DOI: 10.3390/life12111710
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Lens Tear Meniscus Height, Lipid Layer Pattern and Non-Invasive Break-Up Time Short-Term Changes with a Water Gradient Silicone Hydrogel Contact Lens

Abstract: To evaluate pre-lens tear film volume, stability and lipid interferometry patterns with a silicone hydrogel water content contact lens, a novel, noninvasive, ocular-surface-analyzer technology was used. A prospective, longitudinal, single-center, self-control study was performed in daily or monthly replacement silicone hydrogel contact lens wearers. A tear film analysis was achieved with the Integrated Clinical Platform (ICP) Ocular Surface Analyzer (OSA) from SBM System. The subjects were reassessed, with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 40 publications
3
11
0
Order By: Relevance
“…41 Despite the fact that FBUT and non-invasive tear break-up time (NIBUT) are both techniques to measure the stability of the tear film, and their values are not interchangeable, a reduction in both parameters has been found after CL use. 16,41 Additionally, the disruption of the tear film layers did not seem to affect the lipid layer thickness, regardless of the wearing time or CL material, as reported in both the present study and previous investigations. 16 A newly developed contact lens material (verofilcon A), composed of a core of silicone-hydrogel material having a water content of 33% and an outer surface with an 80% water content, showed good pre-CL NIBUT values during lens wear, when compared with other daily disposable silicone-hydrogel and hydrogel CLs.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…41 Despite the fact that FBUT and non-invasive tear break-up time (NIBUT) are both techniques to measure the stability of the tear film, and their values are not interchangeable, a reduction in both parameters has been found after CL use. 16,41 Additionally, the disruption of the tear film layers did not seem to affect the lipid layer thickness, regardless of the wearing time or CL material, as reported in both the present study and previous investigations. 16 A newly developed contact lens material (verofilcon A), composed of a core of silicone-hydrogel material having a water content of 33% and an outer surface with an 80% water content, showed good pre-CL NIBUT values during lens wear, when compared with other daily disposable silicone-hydrogel and hydrogel CLs.…”
Section: Discussionsupporting
confidence: 85%
“…13 The use of CLs also alters tear film stability and tear volume, with decreased values being observed after CL removal. [14][15][16] Following the suggestion made by the TFOS CLD workshop, this randomised clinical trial aimed to assess the impact of a daily disposable silicone-hydrogel CL (somofilcon A) on symptoms, tear film dynamics and ocular surface integrity, when compared with non-CL wearers over the course of a month, paying special attention to changes in LWE and its potential implications for CLD.…”
Section: Introductionmentioning
confidence: 99%
“…6 These theoretical predictions were recently confirmed in a clinical study, which demonstrated that Lehfilcon A wear resulted in a significant change in mean (±SD) pre-lens NIBUT from 15.19 ± 9.54 to 21.27 ± 11.97 s (p < 0.01). 7 Further confirmation of these theoretical expectations was provided by Fujimoto et al, 8 where the pre-lens TF with Delefilcon A (θ ≤ 20°) remained stable at 4.1 ± 2.3 s versus Narafilcon A (θ = 70°) with a value of 2.7 ± 1.6 s after ≥5 h wear for 1 month. 5,6 Lateral shearing interferometry also demonstrated higher TF surface quality for Delefilcon A compared with Narafilcon A (a hydrogel lens with higher bulk water content but lacking water gradient), thus emphasising the importance of the hydration and structure of the CL surface.…”
mentioning
confidence: 65%
“…All materials were described in a previous study [22]. Only listed below: Clinical Platform (ICP) Ocular Surface Analyzer (OSA) from SBM System ® (Orbassano, Torino, Italy), Nonmydriatic infrared meibography digital fundus camera Cobra ® HD (Construzione Strumenti Oftalmici CSO ® , Firenze, Italy), Contact Lens Dry Eye Questionnaire 8 (CLDEQ-8) [13,14] and the Standard Patient Evaluation of Eye Dryness (SPEED).…”
Section: Methodsmentioning
confidence: 99%